The Concept of Truth In American Pragmatic Philosophy and Significance for Vietnam - Thoa Nguyen Van; Hanh Than Thi (Kalagatos)
Pragmatism, a distinctive American school of thought, emerged in the late nineteenth century with key representatives such as C. Peirce, W. James, and J. Dewey. This school of philosophy emphasizes the practical value of knowledge and promotes effective action. In pragmatism, the concept of truth is central, determined not by objective correspondence but by practical utility. Peirce considered truth as the result of establishing stable beliefs, James equated truth with utility, and Dewey considered truth as a cognitive tool for solving problems. Although it brings considerable value in promoting practical and innovative thinking, pragmatism also faces limitations when it overemphasizes the subjectivity of truth. Therefore, a comprehensive study of this concept is essential to better understand its impact on modern knowledge and practice.